Current perspectives on dental adhesion: (2) Concepts for operatively managing carious lesions extending into dentine using bioactive and adhesive direct restorative materials - Richard M. Foxton (Elsevier, 2020)
This article reviews the current concepts for operatively managing carious lesions extending into dentine with minimal removal of tooth structure and restoring with dentine adhesives and direct composite resin. It looks sequentially at the operative steps involved including remineralisation with bioactive cements, bonding to caries-affected dentine including smear-layer modification using HOCl, creation of an acid-base resistance zone,steps to optimise the performance of all-in-one adhesives, and incremental placement of direct composite resin to improve bond strengths to cavity floor dentine. It explores how understanding the phenomenon of colour-shifting at the composite resin-enamel/dentine restoration borders can help in creating near "invisible" restoration margins through a "chameleon" effect. With the increased risks of transmission of Covid-19 when aerosol generating procedures are carried out in Dentistry, following a minimally invasive approach to managing dental caries should be given serious consideration.